Strain Coupling and Dynamic Relaxation in a Molecular Perovskite‐Like Multiferroic Metal–Organic Framework. (13th November 2018) - Xin, Lipeng; Zhang, Zhiying; Carpenter, Michael A.; Zhang, Ming; Jin, Feng; Zhang, Qingming; Wang, Xiaoming; Tang, Weihua; Lou, Xiaojie
Abstract: Magnetic metal–organic frameworks (MOFs) with a perovskite structure AMX3 are emerging single‐phased multiferroics with different sources of magnetic and electric ordering. However, the atomic mechanism underlying the multiple ferroic coupling is convincingly clarified. In this work, large single crystals of [(CH3 )2 NH2 ][Ni(HCOO)3 ] are synthesized and shown to exhibit a first‐order ferroelectric phase transition at ≈178 K during heating and at ≈151 K during cooling, as confirmed by temperature‐dependent differential scanning calorimetry, Raman scattering, and X‐ray diffraction studies. Resonant ultrasound spectroscopy (RUS) is used to investigate the elastic and anelastic properties between 5 and 300 K. The RUS results show an abrupt disappearance of resonance peaks above the ferroelectric transition point of ≈178 K. This is probably due to the unfreezing of dimethylammonium cation motion which couples with local strain. Small changes in elastic properties associated with two known magnetic transition at ≈35 and ≈15 K, respectively, are indicative of weak magnetoelastic coupling. An apparent peak in acoustic loss accompanying the canted antiferromagnetic ordering (≈35 K) and spin reorientation transition (≈15 K) is attributed to dynamical magnetoelastic coupling on the RUS time scale of ≈10 −6 s. In comparison with the same MOF structures containing Mn 2+ and Co 2+, the smaller Ni 2+ ions effectively generate an internal chemical pressure and induce a compressed ion force on the anion frameworks. This study opens up a new landscape to explore possibilities for ferroic‐order coupling in molecular MOFs. Abstract : A type‐I multiferroic phase of [(CH3 )2 NH2 ][Ni(HCOO)3 ] creates significant elastic and anelastic anomalies associated with the ferroelectric and magnetic ordering transition. The overlapping strains, from separated ferroic ordering parameters, could provide a mechanism for strong magnetoelectric properties in nickel‐based molecular multiferroics.